Spiritual practices of zen buddhism in the conditions of globalization challenges of modern times - Олександр Донець (Cхід)
The article studies the specifics of Zen Buddhism spiritual practices that influence the spread of their popularity in the contemporary Western globalised world. Zen Buddhism insists on the need for inner spiritual experience, which is directly opposed to authority and external revelation. Zen Buddhism primarily emphasises individual effort in overcoming the separation of the world into opposites, which is the result of the thinking activity. The difference between the religious system of Zen Buddhism is that Zen Buddhism, with its enlightenment, does not depend on sacred books and texts (as, for example, in Christianity, which formed the Western world system); Zen is also primarily non-verbal. The experience of enlightenment cannot be shared with others. Zen practice is a cultivated path, which at the same time has no ultimate goal or meaning; here the path (life in the inevitable) is already a "satori" here and now, which constantly flows through human existence. The relevance and novelty of the study are due to the highlighting of the features of spiritual practices of Zen Buddhism as a way of self-knowledge of a person, "returning to oneself", which ensures its active spread in modern Western society. It is determined that the essence of Zen Buddhism mysticism is that the most real is the abstract, and vice versa. The whole system of spiritual practices is the product of this essential inner spiritual experience. This mysticism often prevents us from measuring the depth of the Eastern mind in terms of Western rationalism because it denies logical analysis by its very nature. The Eastern mind is synthetic. It does not attach too much importance to insignificant trivialities. Still, it strives for an intuitive understanding of the whole, which reaches the spiritual philosophy of Zen in the daily practical challenges of the globalised world. The features of the influence of the spiritual system of Zen Buddhism on Japanese art are also analysed. The conclusions underline that Zen Buddhism has had a significant impact both directly on the religious and cultural life of the Japanese and world culture in general. The popularity of the spiritual practices of Zen Buddhism in Western society is due to their idea of breaking a person out of the subject-object dichotomy, which leads to the separation of the spiritual essence of man, and causes social conflicts. Zen has unique aesthetics, which include a high appreciation of moderation, asymmetry, imperfection, simplicity, and naturalness. In simple beauty and simplicity (transformation of "poverty" into a kind of minimalism), the Japanese find a unique charm and a source of true beauty.